AB1153 Assessment of the Inmunogenic Response to the Vaccines in Patients with Biological Therapy. Initial Study Data Rier. (9th June 2015) - Alcocer, P.; Navio, M.T.; Maria Dolores, M.; Castro, P.; Yuste, J.E.; Muñoz-Fernández, S.
Abstract : Background: Patients with rheumatic disease, especially if they are under biological therapy, are more likely to suffer infections. Because of that, there are a vaccine recommendations. Nevertheless, the effectiveness of this vaccines is unknown and it seems to be affected by the treatment used. Objectives: To asses the response to the Influenza (Influ) virus A and B, and the response to hepatitis B virus (HBV) in patients with biological therapy. Methods: Multicenter study which includes patients with the following guideline:older than 18 years with diagnosis of Rheumatoid arthritis (RA), Spondiloarthritis (SpA), Psoriasic arthritis (PsoA), Psoriasic (Pso), inflammatory intestinal disease (IID), or connectives. All of them coming from hospitals where The Central Laboratory of the Region of Madrid provides services. This patients must be being treated with Infliximab (IFX), Adalimumab (ADA), Etanercept (ETA), Certolizumab (CERTO), Golimumab (GOLI), Tocilizumab (TOCI), Abatacept (ABATA), Rituximab (RTX), Ustekinumab or any other biological therapy, or will iniciate in the period of this study.The response to a flu vaccine was measured by detecting antibody IgG against Influ A and B by ELISA technique at the beginning of the study and at 6 weeks from the vaccination. The same from HBV, it was measured the HbSAb at the beginning and 6 weeks after vaccination. The statistical analysis was made by the statistical system SPSS. Results: Data from 96 patients 63 of which (65.6%) were women with an average age of 48.4±12.8 years and a disease presence for 10.4±19 years. Among all patients, 34/96 (35.4%) were AR, 35/96 (36.5%) SpA, 14/96 (14.6%) A.PSO, 3/96 (3.1%) PSO, 2/96 (2, 1%) IBD, 8/96 (8.3%) other diseases. Biological treatment duration at the time of inclusion was 22.3±21 months. Forty-five (46.8%) and Seventeen (17.7%) had concomitant DMARDs and corticosteroids, respectively. Of the 82 patients treated with DMARDs 75.5% had methotrexate. The biological treatments received were: 9.4% IFX; 31.3% ADA; 25% ETA; CERTO 2.1%; GOLI 11.5%; RTX 12.5%; TOCI 7.3%, 1.04% 1.04% Other Fold.The 52.1% of patients had been vaccinated against influenza the previous year; 54.1% had been previously vaccinated against HBV, 81% of which had received 3 doses. 16/47 of these (34%) had AcHbS>10 at baseline.Antibodies titer was positive from 71.8% and 44.8% for InfluA and InfluB respectively at baseline. After vaccination, 6/96 (6.2%) had seroconverted for Influ A and 4/96 (4.2%) for InfluB. Failed to parse differences in response to flu or HBV among treatments due to the small number of respondents.The rate of adverse effects associated to the administration of vaccines was 7.3% and a infection rate of 2.1% from October to December 2014. Conclusions: The number of patients completing vaccination according to standard is lower than expected. The response to HBV vaccination in these patients is very low and lower than expected in flu vaccination. More immunogenic vaccines against influenza are needed, and determine HbSAb after completing vaccination to see the necessity of booster or even of a second vaccination cycle in non-responder patients. Disclosure of Interest: P. Alcocer Grant/research support from: This project has received funding of Pfizer, SORCOM-MSD grant and has applied for a grant from the European University, M. T. Navio: None declared, M. Maria Dolores: None declared, P. Castro: None declared, J. Yuste: None declared, S. Muñoz-Fernández: None declared